2023
DOI: 10.55275/jposna-2023-731
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid MRI Protocol for Acute Pediatric Musculoskeletal Infection Eliminates Contrast, Decreases Sedation, Scan and Interpretation Time, Hospital Length of Stay, and Charges

Abstract: Introduction: Acute musculoskeletal infections (MSKi) affect >1:6000 children in the United States annually, which could lead to arthritis, chronic infection, limb deformity, and even death. MRI is the gold standard for MSKi diagnosis but traditionally requires contrast and anesthesia, delaying results and slowing treatment decision-making. A rapid MRI protocol is an unsedated MRI with limited non-contrast sequences optimized for fluid detection and diffusion-weighted images to help identify abscesses. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…2, orange line). This is a unique problem for countries where pediatric healthcare depends on a personal insurance plan 13,22 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2, orange line). This is a unique problem for countries where pediatric healthcare depends on a personal insurance plan 13,22 .…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen publications were identified that met criteria by introducing a clinical care innovation and reporting its impact on LOS 12,13,[29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Table III). Studies that only explored the efficacy of shorter antibiotic treatment have not been included as this is previously established information.…”
Section: Clinical Care Innovations To Streamline Inpatient Care and R...mentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, it would be beneficial to develop new tools to decrease the time to obtain preoperative MRI. Several academic centers are developing rapid MRI sequence protocols that show promise in decreasing the need for anesthesia and time to surgery [ 25 ]. Our data suggest that patient outcomes are not adversely affected by obtaining preoperative MRI despite the delay in time to OR.…”
Section: Discussionmentioning
confidence: 99%